Initial understanding and assessment of role of oceanographic features for ferromanganese crusts and nodules in the East Vietnam Sea - Long, Bui Hong; Thu, Phan Minh; Trung, Nguyen Nhu (Vietnam Journal of Marine Science and Technology, 2020)
The iron and manganese content in marine water is very small but the volume of ferromanganese nodules contributes 30% of the total mass of polymetallic nodules and crusts in marine and ocean floor. This suggests that the process of enrichment of ferromanganese crusts and nodules is not only contributed by chemical processes but also by oceanographical and biological processes. The article indicates the initial results of analyzing oceanographic, biological, and environmental features to understand their roles in the growing ferromanganese crusts and nodules and to predict the distribution of ferromanganese crusts and nodules in the East Vietnam Sea. As a result, ferromanganese crusts and nodules in the East Vietnam Sea can be distributed in the continental slopes, where upwelling and downwelling currents occur, to ensure enough dissolved oxygen concentration for the enrichment of ferromanganese crusts and nodules as well as to meet required conditions for microbial activity, which is involved in these processes. However, due to the limitations of the results of studying the enrichment of ferromanganese crusts and nodules in the East Vietnam Sea, the paper just shows the prediction of the distribution of ferromanganese crusts and nodules. Thus, it is necessary to carry out the expedition for enrichment processes of ferromanganese crusts and nodules and to determine the factors that impacted the growing ferromanganese crusts and nodules in the East Vietnam Sea.